Prevalence of Dental Anomalies (Mesiodens and Enamel Hypoplasia) Among Primary School Children in Badra/Iraq - Sanaa Rasheed Abd Al-Aaloosi1, Maitha Sameer Kadhim2, Basma Fathi Alanbari3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Dental anomalies considered as one of the developmental defects during teeth formation caused by both genetic and environmental factors which responsible for notable deviation from normal size, color, number, contour and developmental degree. The aim of this study was to determine prevalence of defect in number (hyperdontia or mesiodens teeth) and structural defect (enamel hypoplasia, localized and generalized,) among primary school children.Material and methods: A cross sectional study that comprises data from 403 boys and 411 girls; a primary school students aged from 5-12 years with a total of 814 student; was conducted in Badra/ Iraq.Results: The study shows a prevalence rate of a mesiodens from 814 students was 0.49% and it represented more frequently in males more than females with a ratio of 3:1. While, the prevalence of enamel hypoplasia was estimated to be 0.86 % among the observed population, it observed more in girls than in boys, with the proportion being around 1: 1.333 male: female ratio.Conclusion: the prevalence of dental anomalies was found to be more in males than in females and most of the cases found in age group between 8-10 years old. Routine checkup for these anomalies during primary and mixed dentation which can help for early diagnosis and detection of these disorders that will help minimizing future complications and give well prognosis.